Bringing madness home : the multiple meanings of home in Janet Frame's Faces in the water, Bessie Head's A question of power and Lauren Slater's Prozac diary - Jäntti, Saara (Jyväskylä : University of Jyväskylä, 2012)
Kodin monet merkitykset naisten hulluuskertomuksissa : Janet Framen Faces in the water, Bessie Headin A question of power ja Lauren Slaterin Prozac diary.
Väitöskirja
World Wide Web.
XLUETTELOITU
Keywords: koti; naiset; mielenterveys; mielenterveyshäiriöt; psykiatrinen hoito; omaelämäkerrallisuus; kirjallisuus; aiheet; hulluus; home; women's madness; psychiatry; gender; literature; space; belonging